Immunometabolism at the Nexus of Cancer Therapeutic Efficacy and Resistance - Traba, Javier; Sack, Michael N.; Waldmann, Thomas A.; Anton, Olga M. (Frontiers in Immunology, 2021)
Constitutive activity of the immune surveillance system detects and kills cancerous cells, although many cancers have developed strageties to avoid detection and to resist their destruction. Cancer immunotherapy entails the manipulation of components of the endogenous immune system as targeted approaches to control and destroy cancer cells. Since one of the major limitations for the antitumor activity of immune cells is the immunosuppressive tumor microenvironment (TME), boosting the immune system to overcome the inhibition provided by the TME is a critical component of oncotherapeutics. In this article, we discuss the main effects of the TME on the metabolism and function of immune cells, and review emerging strategies to potentiate immune cell metabolism to promote antitumor effects either as monotherapeutics or in combination with conventional chemotherapy to optimize cancer management.